Training on Customer Driven Value Marketing in Improving Customer Satisfaction on SME Products - Nur Hidayah; Darrell Christopher; Darren Jonathan (International Journal of Social Science and Community Service, 2024)
Customer driven value is a marketing approach that takes social and environmental responsibility into account, while meeting consumer needs and business interests. It also emphasizes the importance of caring for and increasing the capacity of future generations to meet their needs. The activity partner is engaged in a culinary business located on the east ring road, Mulyo 2 RT 28 Kel Talang Bakung, Paal Merah Jambi. In its activities, it faces problems, especially in terms of customer driven value. This activity aims to support partners in increasing understanding of marketing based on the value that must be provided to customers, so that partners can increase competitive advantage. The method of this activity focuses on customer driven value, especially in terms of how business owners interact with the environment and related interests. This strategy also assists partners in efforts to increase the value of products aimed at customers by providing more experiences that can increase customer satisfaction. The activity method is carried out through offline training through the zoom application. This activity expects partners to increase value to customers in marketing their products. The results of the activity show that the implementation of the training went smoothly, the partners enthusiastically accepted the material presented by the PKM leader.